2005
DOI: 10.1002/ijc.21064
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid cancer and multiple primary tumors in the SEER cancer registries1

Abstract: Thyroid cancer incidence rates have increased steadily in the United States and elsewhere. Radiation exposure at a young age is a strong risk factor, but otherwise the etiology is unclear. To explore etiologic clues, we studied the risk of thyroid cancer after an earlier primary cancer, as well as the risk of developing multiple primaries after an earlier thyroid cancer in the U.S. Surveillance, Epidemiology and End-Results (SEER) cancer registries program . In 2,036,597 patients diagnosed with any invasive ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
134
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 43 publications
(48 reference statements)
9
134
0
2
Order By: Relevance
“…Especially, the relation between these glycoproteins and matrix metalloproteinases, critical for the development of wound healing and cancer progression, is suggestive for a common genetic base. Ronckers et al recently published a large report on thyroid cancer and multiple primary tumors (18). They studied the risk of thyroid cancer after an earlier primary cancer, as well as the risk of developing multiple cancers after an earlier thyroid cancer in the US, using the cancer registry program of more than 2 million patients.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, the relation between these glycoproteins and matrix metalloproteinases, critical for the development of wound healing and cancer progression, is suggestive for a common genetic base. Ronckers et al recently published a large report on thyroid cancer and multiple primary tumors (18). They studied the risk of thyroid cancer after an earlier primary cancer, as well as the risk of developing multiple cancers after an earlier thyroid cancer in the US, using the cancer registry program of more than 2 million patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increased incidence of thyroid carcinoma following breast cancer is also known [3]. Ronckers et al say that patients of <40 years of age at diagnosis of thyroid cancer have a 39% risk of second cancer, in contrast to 6% in older patients [4]. In the same study, several other cancer sites showed significantly increased risks in both directions, including salivary glands, prostate, breast, kidney, scrotum, brain and leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of articles in the 1950s by Seidlin, the father of radioiodine treatment for thyroid carcinoma, and coworkers [31][32][33] it was well documented that there is an excess risk of leukaemia after treatment with high cumulative activities of radioiodine [34,35], correlating with the administered total radioiodine activity [36]. In practice this means that this excess risk only materializes in patients with metastatic disease after repeated (high-activity) treatments.…”
mentioning
confidence: 99%
“…An increased risk of other malignancies of organs such as the salivary glands, the breasts, the stomach or even the prostate has also been reported. It is, however, unclear how much of this risk RRA treatment is responsible for, as it has been noted in multiple studies that such carcinomas are observed in excess both before and after the diagnosis and treatment of DTC [34,37]. The latter observation suggests that aetiological similarities and possible treatment effects are responsible for this excess in secondary malignancies [34].…”
mentioning
confidence: 99%
See 1 more Smart Citation